Formation features of composite electrochemical nickel and nanostructured zirconium boride coatings - L. A. Degtyar; I. S. Ivanina; I. Yu. Zhukova (Advanced Engineering Research)
Introduction. The electrodeposition of composite electrochemical coatings from electrolyte-colloid nickel plating containing ultradisperse zirconium boride powder is studied. The work objectives are as follows: to study mechanical-and-physical properties of the composites based on nickel and nanostructured zirconium boride, and to determine optimal conditions for the application of such electrochemical coatings.Materials and Methods. Microhardness of composite electrochemical coatings was measured using PMT-3 microhardness tester on samples with the layer thickness of 30 μm under the indentation load of 100 g. A three-ball machine was used to determine wear resistance of the coatings. Sample tests were carried out under dry friction modes and with the use of 3% RV coolant. WSD values were measured by MIR-3 TU 3-3.1954-86 microscope. To determine the internal stresses in the coating, we used a flexible cathode method up to GOST 9.302-88.Research Results. The electrolyte-colloid composition and modes of electrodeposition of composite nickel - nanostructured zirconium boride coatings are developed. Mechanicaland-physical properties (microhardness, wear resistance and internal stresses) of the obtained composite electrochemical coatings are analyzed. Recommendations for use of the developed electrolyte and the application of a composite coating on machine parts for their surface hardening are formulated.Discussion and Conclusions. Ni–ZrB2 CEC (composite electrochemical coating) has high microhardness (10–11 hPa at the indentation load of 100 g), which exceeds the microhardness of pure nickel by 1.5–2 times. As the microhardness increases, the internal stresses of Ni–ZrB2 CEC decrease. The proposed coatings were compared to chromium ones deposited from the environmentally hazardous electrolytes. The wear resistance of Ni–ZrB2 CEC is 2–5 times higher than that of chromium coatings. Thus, instead of chromic coatings, it is recommended to use the proposed composition for surface hardening of parts of the specialty machinery and industrial equipment